Zur alten und neuen Logik der Agrarpolitik in Europa: Gibt es effektive Steuerungsmechanismen einer nachhaltigen Landwirtschaft? - Christian H. C. A. Henning; Michael Grunenberg (Wirtschaftsdienst, 2024)
– Few policies have been as heavily criticised as European agricultural policy. Consequently, since its establishment in 1962, it has been in a continuous process of reform, encompassing six major reforms in the last 30 years alone. The central question arises: What is the logic behind the endless reform history of EU agricultural policy? Are agricultural reforms fundamentally a logical consequence of changing objectives or structural conditions, and thus dynamically efficient? Or do they represent a sequence of unsuccessful political learning processes and thus a perpetual policy failure? The latter implies that there are more efficient policy options that would be politically feasible given the democratic power relations and decision-making processes in place.
Keywords: Q15; Q18; Q57; 330; Agrarpolitik; Landwirtschaft; Nachhaltige Entwicklung; EU-Staaten; Agrarpolitik; Landwirtschaft; Nachhaltige Entwicklung; EU-Staaten